Right to Be Forgotten for Child Victims of Electronic Sexual Violence - Rahmatiah Irwan; Aulya Nisa'; Anggun Retno Wardani; Agrita Permata Sari; Azzura Fathanul Umara; Rivana Tesalonika Taroreh (Magister Hukum Universitas Semarang, 2026)
This study analyzes the implementation of the Right to Be Forgotten (RTBF) as a legal protection instrument for children victims of electronic-based sexual violence (KSBE). The phenomenon of KSBE in Indonesia shows a significant increase, with women and children as the main victims. Sexually charged content stored in digital spaces triggers prolonged re-victimization because it is difficult to remove. Although RTBF has been recognized normatively through the TPKS Law, ITE Law, Child Protection Law, and Personal Data Protection Law, its implementation is still partial and not yet effective. The main obstacles include the absence of clear technical rules, formalistic and slow legal procedures, technical limitations in cross-jurisdictional elimination, and multiple interpretations of norms. This condition causes the children of KSBE victims to experience structural victimization, where the failure of the state to provide a mechanism for removing content adds to the psychological and social burden of the victims. A juridical-normative approach with radical victimization analysis shows that RTBF has not been positioned as a victim's substantive right, so protection has not been fully in favor of the principle of the best interests of the child. This research emphasizes the need for operational legal reforms: a rapid administrative mechanism for content removal, strict sanctions for non-compliant digital platforms, and multi-sector coordination between law enforcement agencies, Kominfo, and child protection agencies. The main findings of the study are the placement of RTBF as a substantive instrument to protect children victims of KSBE in the digital era, strengthening the principle of the best interests for children, while affirming the role of the state in stopping the cycle of digital victimization. The novelty of the research lies in the integration of radical legal, digital, and victimology analysis to formulate concrete technical and procedural recommendations for child protection in the digital space. Keywords: children; electronic-based sexual violence; legal protection; right to be forgotten; victimologyn